2020
DOI: 10.1021/acs.orglett.9b04237
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Radical Selectivity in Biphasic Systems

Abstract: Aryl radicals generated in the aqueous phase of biphasic mixtures haveregardless of a comparably low polarity a strong preference to react with aromatic substrates in the aqueous phase and not to undergo phase-transfer into a lipophilic phase, independent from the presence of a surfactant. These results represent an important prerequisite toward future studies in biological systems, which typically consist of various compartments of either hydrophilic or lipophilic character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Because potassium persulfate was water soluble, both 1 and 2 had to be transferred into aqueous solution to react with potassium persulfates. 19 This proposal is also in accord with the experimental results that no products of sp 2 C–H phosphorylation are detected, which are the main products in the previous radical systems. 20 Finally, cross couplings between 5 and 6 produce 3 ( Scheme 2 ).…”
supporting
confidence: 84%
“…Because potassium persulfate was water soluble, both 1 and 2 had to be transferred into aqueous solution to react with potassium persulfates. 19 This proposal is also in accord with the experimental results that no products of sp 2 C–H phosphorylation are detected, which are the main products in the previous radical systems. 20 Finally, cross couplings between 5 and 6 produce 3 ( Scheme 2 ).…”
supporting
confidence: 84%
“…Only the 4‐methoxy derivative 5 h turned out as too unreactive, at which the low reactivity resulting from donor substitution could not be overcome by irradiation [19a] . A low yield of 25 % was observed for the functionalization of 1,1‐diphenylethene ( 3 b ), which can partly be explained by insufficient solubility and ineffective phase transfer of the aryl radical [22] …”
Section: Resultsmentioning
confidence: 99%
“…[19a] Al ow yield of 25 %w as observed for the functionalization of 1,1-diphenylethene (3b), which can partly be explained by insufficient solubility andi neffective phase transfer of the aryl radical. [22] Regarding the desired biocompatibility of the carbohydroxylation,m easurements of the pH value during the synthesis of 5a (Scheme 3) revealed that the pH value drops from an initial value of 3tovalues around1.5 over the reaction course.While the initially acidic conditions can be attributedt o traces of tetrafluoroboric acid in the diazonium tetrafluoroborate salt,t he increasing acidity during product formation is caused by the mechanism,w hich liberates protons (6!5, Scheme 2). This drawback can however be balanced by the addition of potassium acetate (1.5 equiv) to the reaction mixture.…”
Section: Entrymentioning
confidence: 99%
“…Heinrich and co‐workers [33] studied aryl radical generation in a biphasic mixture and stated that in a biphasic system, aryl radicals generated in the aqueous phase tend to react with aromatic substrates in the aqueous phase without going to the lipophilic phase, even in the presence of a surfactant (Scheme 10). This could be important in biological systems due the presence of several lipophilic and hydrophilic compartments [34–37] …”
Section: Aryl Radicals From Aryldiazonium Salts Under Thermal Conditionsmentioning
confidence: 99%